Reactive oxidants and myeloperoxidase and their involvement in neutrophil extracellular traps - Parker, Heather; Winterbourn, Christine (Frontiers in Immunology, 2013)
Neutrophils release extracellular traps (NETs) in response to a variety of inflammatory stimuli. These structures are composed of a network of chromatin strands associated with a variety of neutrophil-derived proteins including the enzyme myeloperoxidase (MPO). Studies into the mechanisms leading to the formation of NETs indicate a complex process that differs according to the stimulus. With some stimuli an active nicotinamide adenine dinucleotide phosphate (NADPH) -oxidase is required. However, assigning specific reactive oxygen species involved downstream of the oxidase is a difficult task and definitive proof for any single oxidant is still lacking. Pharmacological inhibition of MPO and the use of MPO-deficient neutrophils indicate active MPO is required with phorbol myristate acetate as a stimulus but not necessarily with bacteria. Reactive oxidants and MPO may also play a role in NET-mediated microbial killing. MPO is present on NETs and maintains activity at this site. Therefore, MPO has the potential to generate reactive oxidants in close proximity to trapped micro-organisms and thus effect microbial killing. This brief review discusses current evidence for the involvement of reactive oxidants and MPO in NET formation and their potential contribution to NET antimicrobial activity.